Cistrome-based Cooperation between Airway Epithelial Glucocorticoid Receptor and NF-κB Orchestrates Anti-inflammatory Effects - Kadiyala, Vineela (J Biol Chem, 2016)
Antagonism of pro-inflammatory transcription factors by monomeric glucocorticoid receptor (GR) has long been viewed as central to glucocorticoid (GC) efficacy. However, the mechanisms and targets through which GCs exert therapeutic effects in diseases such as asthma remain incompletely understood. We previously defined a surprising cooperative interaction between GR and NF-κB that enhanced expression of A20 (TNFAIP3), a potent inhibitor of NF-κB. Here we extend this observation to establish that A20 is required for maximal cytokine repression by GCs. To ascertain the global extent of GR and NF-κB cooperation, we determined genome-wide occupancy of GR, the p65 subunit of NF-κB, and RNA polymerase II in airway epithelial cells treated with dexamethasone, TNF, or both using chromatin immunoprecipitation followed by deep sequencing. We found that GR recruits p65 to dimeric GR binding sites across the genome and discovered additional regulatory elements in which GR-p65 cooperation augments gene expression. GR targets regulated by this mechanism include key anti-inflammatory and injury response genes such as SERPINA1, which encodes α1 antitrypsin, and FOXP4, an inhibitor of mucus production. Although dexamethasone treatment reduced RNA polymerase II occupancy of TNF targets such as IL8 and TNFAIP2, we were unable to correlate specific binding sequences for GR or occupancy patterns with repressive effects on transcription. Our results suggest that cooperative anti-inflammatory gene regulation by GR and p65 contributes to GC efficacy, whereas tethering interactions between GR and p65 are not universally required for GC-based gene repression.